Pemanfaatan Aplikasi Shopee dan Tiktok Sebagai Media Pemasaran Produk UMKM Parcel - Titi Kusumadewi, Riya; Ti’anatud Diniati, Bintis; Na’imatus Sahira, Nazwa; Affrilya Laffaysza, Frizcha (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The development of digital technology in the modern era has brought significant changes to MSME marketing strategies, including the utilization of social media and e-commerce as product promotion media. This research was conducted at a Parcel MSME located in Batangsaren Village, Kauman District, Tulungagung Regency, East Java. The purpose of this activity was to determine the utilization of Shopee and TikTok in supporting the marketing of parcel MSME products, to identify the impact of using these applications on marketing improvement, and to analyze the obstacles faced by business owners in their implementation. The method used in this activity was a qualitative descriptive approach with data collection techniques consisting of observation, interviews, and documentation. The data were obtained directly through interviews with the MSME owner and observations of the marketing activities carried out. The results showed that the utilization of Shopee and TikTok had a positive impact on the marketing of parcel MSME products. Shopee helped simplify the sales process and expand market reach, while TikTok was effectively used as a creative promotional medium through short videos and live streaming that increased consumer buying interest. However, MSME owners still faced several obstacles, such as limited digital marketing skills, difficulties in creating attractive promotional content, intense online market competition, and limited supporting facilities. Therefore, improving digital understanding and skills is necessary so that the utilization of digital platforms can be carried out optimally and sustainably.